Implementation of Matrix Organizational Structure in Global Account Management: Challenges and Opportunities - Muslim Marpaung; Irma Suryani Lubis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Matrix organizational structures are increasingly being used by multinational companies in response to the complexities of global account management (GAM). This article explores the challenges and opportunities in implementing a matrix structure for GAM through a qualitative, case study-based approach. The study was conducted across four global companies in the technology and manufacturing sectors. The results show that matrix structures enhance cross-functional and cross-regional coordination, but also create role conflict, authority ambiguity, and high communication burden. This study provides strategic insights for top management to balance the need for global integration and local adaptation in the context of global strategic account management.